Social Media Marketing Initiatives and Brand Loyalty - Rai, Bharat; Dahal, Rewan Kumar (Nepal Journal of Multidisciplinary Research, 2024)
Background: Social media advertising strategies have radically changed how brands interact with consumers and cultivate brand loyalty. The study's principal objective was to identify the influence of social media marketing activities on consumer brand loyalty toward shopping goods. Methods: The study used primary data from a structured survey questionnaire with the six-point Likert scale sent to Nepalese customers. The study's sampling was convenient, and the Kathmandu-based location was chosen as the sample site. The study's population was the consumers of consumer shopping goods. People who purchase consumer shopping items were given 600 surveys, but only 395 usable questionnaires were collected. Results: Through the path analysis, the influence of the credibility of social media significantly and positively influenced brand loyalty (β = 0.165, p < 0.05). It was also found that the informativeness of social media significantly impacted brand loyalty toward consumer shopping goods (β = 0.130, p < 0.05). Likewise, it was also investigated whether social media entertainment significantly impacts brand loyalty (β = 0.426, p < 0.05) toward consumer shopping goods in the Nepalese market. Conclusion: By leveraging the power of social media venues to engage with customers, deliver pertinent content, and create personalized experiences, businesses may cultivate a strong emotional connection with their target audience, increasing brand loyalty and trust. Novelty: The study results show how future researchers and business people can look at the new conditions for market growth.